2014
DOI: 10.3201/eid2003.130745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ImportedPlasmodium ovale curtisiandP. ovale wallikeriInfections among Patients in Spain, 2005–2011

Abstract: Sequencing data from Plasmodium ovale genotypes co-circulating in multiple countries support the hypothesis that P. ovale curtisi and P. ovale wallikeri are 2 separate species. We conducted a multicenter, retrospective, comparative study in Spain of 21 patients who had imported P. ovale curtisi infections and 14 who had imported P. ovale wallikeri infections confirmed by PCR and gene sequencing during June 2005–December 2011. The only significant finding was more severe thrombocytopenia among patients with P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 30 publications
(46 reference statements)
7
68
1
Order By: Relevance
“…The low performance of our PCR for the detection of P. ovale reflects the limitations of the primers and probe used in distinguishing between the two P. ovale subspecies, P. ovale curtisi and P. ovale wallikeri. 19,21,22 Since the primers we used for the detection of P. ovale detect only P. ovale curtisi, we indirectly confirmed that the four detected cases were P. ovale curtisi and the other two undetected ones were P. ovale wallikeri. Overall, the introduction of molecular diagnostics demonstrated a remarkably higher share (13.3%) of P. ovale among the Plasmodium species imported into Serbia than considered before the introduction of qPCR (1%).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The low performance of our PCR for the detection of P. ovale reflects the limitations of the primers and probe used in distinguishing between the two P. ovale subspecies, P. ovale curtisi and P. ovale wallikeri. 19,21,22 Since the primers we used for the detection of P. ovale detect only P. ovale curtisi, we indirectly confirmed that the four detected cases were P. ovale curtisi and the other two undetected ones were P. ovale wallikeri. Overall, the introduction of molecular diagnostics demonstrated a remarkably higher share (13.3%) of P. ovale among the Plasmodium species imported into Serbia than considered before the introduction of qPCR (1%).…”
Section: Discussionsupporting
confidence: 69%
“…This may have been due to the poor quality of the long stored blood samples and DNA degradation, or the inhibition of PCR amplification. 3,19 However, as this sample was positive by species-specific qPCR and RDT for P. falciparum, a technical error is more likely. The false-positive results obtained for a few patients in samples collected after antimalarial treatment may be attributed to the persistence of gametocytes (although sexual stages of Plasmodium were not detected independently of asexual parasites), circulating DNA from therapy-damaged parasites, 20 or to cross-reactivity with homologous DNA of other eukaryotic species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As previously noted, P. ovale wallikeri cases appeared to increase more so than P. ovale curtisi in the past five years, and if this trend were to continue, the lack of Schüffner’s stippling may further hinder interpretation of microscopy and RDT results. The lack of Schüffner’s stippling among P. ovale wallikeri isolates joins other findings that the sub-species have distinguishing clinical characteristics, such as latency and degree of thrombocytopaenia, in addition to their genotype [9, 10]. That said, molecular techniques are still the most accurate and specific method for determining sub-species of P. ovale .…”
Section: Discussionmentioning
confidence: 64%
“…First recognized in 2010, these two sub-species are believed to have diverged one to two million years ago [7, 9]. Clinical differences between the two sub-species have not been clearly elucidated, although there have been differences found in latency period [9] and thrombocytopaenia [10]. At present, it is unknown if the performance of malaria diagnostic tests may differ between the sub-species, causing infection.…”
Section: Introductionmentioning
confidence: 99%